LKPD PEMBELAJARAN BIOLOGI SMP BERBASIS RISET MORFOLOGI DAUN PASCA KEBAKARAN DI LAHAN GAMBUT - Yosi Emelda; Wan Syafi’i; L.N. Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Peatland fires are confirmed to affect ecological balance of ecosystems due to vegetation destruction. The leaves are the first organ of the most flammable. Therefore, the morphological characteristics of plant leaves after the fire are importance to be studied. This reserach aims to produce LKPD Learning VIII class of biological science at Junior High School by utilizing the research findings on the morphological characteristics of plant leaves. For this purpose, a survey was conducted in Rimba Panjang Village, Kampar District, Riau Province in February-October 2017. Quadratic method and purposive sampling technique were used based on post-fire gradient 2009, 2013, 2014, 2015, 2016 and 2017. Leaf morphological characteristics were observed at the dominant sapling level. Data were analyzed descriptively-qualitative. The results obtained were 6 dominant saplings species, i.e Evodia roxburghiana, Acacia mangium, Ilex cymosa, Eugenia pelyta, Macaranga triloba and Cratoxylon arborescens. Morphological Characteristics of Acacia mangium leaves have a hard leaf repeating system compared with other plant leaves. It can be concluded that hard leaf repeats are characteristic of sapling leaf morphology so that it is more susceptible to fire. These characteristics can be utilized for the development of biology science LKPD for VII grade at Junior High School on Environmental Pollution (KD 3.8) and Structure and Function for VIII Grade (KD 3.4). Testing of the use of LKPD that has been generated and the benefits of enriching student learning materials in a classical manner is highly recommended.Keywords : Leaf Morphology, Peat Land, Post Fire, LKPD, Junior High School